The role of growth differentiation factor 15 in the pathogenesis of primary myelofibrosis. (15th August 2015) - Uchiyama, Tatsuki; Kawabata, Hiroshi; Miura, Yasuo; Yoshioka, Satoshi; Iwasa, Masaki; Yao, Hisayuki; Sakamoto, Soichiro; Fujimoto, Masakazu; Haga, Hironori; Kadowaki, Norimitsu; Maekawa, Taira; Takaori‐Kondo, Akifumi
Abstract Growth differentiation factor 15 (GDF15) is a pleiotropic cytokine that belongs to the transforming growth factor‐β superfamily. Elevated serum concentrations of this cytokine have been reported in patients with various malignancies. To assess the potential roles of GDF15 in hematologic malignancies, we measured its serum levels in patients with these diseases. We found that serum GDF15 levels were elevated in almost all these patients, particularly in patients with primary myelofibrosis (PMF). Immunohistochemical staining of bone marrow (BM) specimens revealed that GDF15 was strongly expressed by megakaryocytes, which may be sources of increased serum GDF15 in PMF patients. Therefore, we further assessed the contribution of GDF15 to the pathogenesis of PMF. Recombinant human (rh) GDF15 enhanced the growth of human BM mesenchymal stromal cells (BM‐MSCs), and it enhanced the potential of these cells to support human hematopoietic progenitor cell growth in a co‐culture system. rhGDF15 enhanced the growth of human primary fibroblasts, but it did not affect their expression of profibrotic genes. rhGDF15 induced osteoblastic differentiation of BM‐MSCs in vitro, and pretreatment of BM‐MSCs with rGDF15 enhanced the induction of bone formation in a xenograft mouse model. These results suggest that serum levels of GDF15 in PMF are elevated, that megakaryocytes are sources of this cytokine in BM, and that GDF15 may modulate the pathogenesis of PMF by enhancing proliferation and promoting osteogenic differentiation of BM‐MSCs.